Traditional Chinese medicine in osteoporosis: from pathogenesis to potential activity - Cao, Gang; Hu, ShaoQi; Ning, Yan; Dou, Xinyue; Ding, Chuan; Wang, Lu; Wang, Zeping; Sang, Xianan; Yang, Qiao; Shi, Jiangnan; Hao, Min; Han, Xin (Frontiers in Pharmacology, 2024)
Osteoporosis (OP), characterized by decreased bone mineral density and bone mass, is a systemic bone disease with multiple causes. Besides, osteoporosis along with destruction of bone microstructure and increased of bone fragility. , osteoporosis OP is attributed to multiple causes, including aging, inflammation, diabetes mellitus and other factors induced by adverse effects of medications. If without treatment, osteoporosis OP will further progresswill increase the risk of fracture, which and bring great trouble to human life. Due to the various causes, the treatment of osteoporosis OP is mainly aimed at improving bone metabolism, inhibiting bone resorption and promoting bone formation. Although the currently approved drugs can reduce the risk of fragility fractures in individuals, a single drug has limitations in terms of safety and effectivenessAt present, the common drugs used for the treatment of osteoporosis are hormones or other synthetic drugs that have certain side effects. By contrast, traditional Chinese medicine (TCM) that a characteristic disciplines in China, including syndrome differentiation, Chinese medicine prescription and active ingredientsAs , a characteristic discipline in China, shows unique advantages in the treatment of osteoporosis OP andtraditional Chinese medicine (TCM) with the unique advantage of few side effects has received attentions all over the world. Therefore, tThis review summarized the pathogenic factors, pathogenesis, therapy limitations and advantages of TCM, aiming at providing new ideas for the prevention and treatment of OPosteoporosisOP. summarized the pathogenic factors, pathogenesis and related signaling pathways of osteoporosis. Based on these, we also concluded the effects and possible mechanisms of TCM treatment for osteoporosis based on syndrome differentiation, TCM compound prescriptions, single herbs and TCM active ingredients in the treatment of osteoporosis and provided new ideas for prevention and treatment of osteoporosis.